2023
DOI: 10.1371/journal.pone.0291423
|View full text |Cite
|
Sign up to set email alerts
|

Trend analysis of COVID-19 mis/disinformation narratives–A 3-year study

Bonka Kotseva,
Irene Vianini,
Nikolaos Nikolaidis
et al.

Abstract: To tackle the COVID-19 infodemic, we analysed 58,625 articles from 460 unverified sources, that is, sources that were indicated by fact checkers and other mis/disinformation experts as frequently spreading mis/disinformation, covering the period from 1 January 2020 to 31 December 2022. Our aim was to identify the main narratives of COVID-19 mis/disinformation, develop a codebook, automate the process of narrative classification by training an automatic classifier, and analyse the spread of narratives over time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The interviews and mapping of current initiatives by organisations in the identification of false information found that false information tends to be clustered within social media communities. Another relevant finding was that the use of Artificial Intelligence (AI) shows promise in supporting the identification of false information, as evidenced by the successful AI false information identification system developed by DG JRC (Kotseva et al, 2023). The interviews also revealed that there is a high willingness among institutions to collaborate with EFSA in identifying false information within the scope of this project.…”
Section: Area Overviewmentioning
confidence: 83%
“…The interviews and mapping of current initiatives by organisations in the identification of false information found that false information tends to be clustered within social media communities. Another relevant finding was that the use of Artificial Intelligence (AI) shows promise in supporting the identification of false information, as evidenced by the successful AI false information identification system developed by DG JRC (Kotseva et al, 2023). The interviews also revealed that there is a high willingness among institutions to collaborate with EFSA in identifying false information within the scope of this project.…”
Section: Area Overviewmentioning
confidence: 83%
“…Interpreting these findings would necessitate in-depth analysis, especially to explore the potential factors influencing HL during this period. The diminished self-perception of health knowledge and awareness could at least, in part, stem from widespread misinformation/disinformation in the media and adult discussions during the pandemic [32]. An Australian study has reported a correlation between susceptibility to misinformation and lower health literacy levels [33].…”
Section: Determinants Of Hl Index and Its Changementioning
confidence: 99%